Kesadaran Hukum Pelaku Usaha UMKM terhadap Pembayaran Pajak Air Permukaan Perspektif Maqashid Syariah - Sibagariang, Maya Sari; Rokan, Mustapa Khamal (Universitas Muhammadiyah Ponorogo, 2025)
Tax is the main source of state revenue that is vital to finance public needs and national development. However, the low awareness of taxpayers, including business actors, in paying surface water tax (PAP) causes losses to the national, provincial, and regional treasury. This study aims to analyze the factors that influence business actors not to pay PAP and evaluate their legal awareness through the perspective of Maqashid Syariah. The research method used is empirical law with a quantitative approach. The results of the study indicate that there are four main factors that influence business actors' non-compliance in paying PAP, namely: (1) lack of socialization and understanding of tax obligations, (2) economic problems and high cost burdens, (3) weak law enforcement, and (4) low awareness and legal education. From the perspective of Maqashid Syariah, the legal awareness of business actors in paying PAP must consider the principle of public interest (maslahah). Improvement efforts such as increasing socialization, reducing economic burdens, consistent law enforcement, and increasing legal education are strategic steps to achieve public welfare (al-maslahah al-ammah) and justice. This approach emphasizes the balance between individual rights and social responsibilities, in accordance with the principles of Maqashid Syariah which aims to safeguard public interest (hifz al-mal) and prevent harm (darar). This study provides an original contribution by integrating the perspective of Maqashid Syariah in the analysis of legal awareness of business actors, which has not been widely explored in previous literature. However, this study has limitations, namely the geographical scope is limited to one region, so the findings may not be widely generalized. Recommendations for further research are to expand the scope of the region and involve more variables to deepen the analysis.